Analysis of factors influencing patient delay by patients with pulmonary tuberculosis in Lishui City, Zhejiang Province - Jing Guo; Yin-Ping Feng; Zhong-Da Liu; Shui-Rong Luo; Qian-Yu Wu (BMC Pulmonary Medicine, 2023)
Abstract Objective The purpose of this study was to collect data on the current state of patient delay by patients with tuberculosis (TB) in Lishui City, Zhejiang Province who were under the care of a TB-designated hospital from 2011 to 2021 and to analyze the factors that contribute to this problem in order to provide a scientific basis for the prevention and control of TB. Methods In this observational study, we collected data on patients with pulmonary TB that were reported to the Chinese government's disease prevention and control information system by the Traditional Chinese Medicine Hospital in Lishui City between 2011 and 2021. The data included demographics like age, gender, occupation, household registration, current address, date of symptoms, date of first visit, and etiology results. Multivariate logistic regression analysis was used to analyze the factors influencing patient delay by patients with pulmonary TB. Results There were 3,190 cases of pulmonary TB treated in a TB-designated hospital in Lishui City, Zhejiang Province, between 2011 and 2021. Of these, 2,268 involved patient delay, with the delay rate of 71.10% and the median (Q25, Q75) days of patient delay being 36 (25, 72) days. Results of multivariate logistic regression analysis indicated the presence of risk factors-age > 60 years old (OR = 1.367, 95% CI: 1.144 ~ 1.632), pathogen positive (OR = 1.211, 95% CI: 1.033 ~ 1.419), and employed as peasants (OR = 1.353, 95% CI:1.144 ~ 1.601) for patient delay in patients with pulmonary TB. Patients with diabetes mellitus made up 64.94% of the pulmonary TB population, which was lower than the 71.58% of patients without diabetes mellitus (χ2 = 4.602, P = 0.032). Additionally, the presence of diabetes mellitus may be a protective factor in patient delay in patients with pulmonary TB (OR = 0.641, 95% CI: 0.481 ~ 0.856). Conclusion High rates of patient delay, age > 60 years old, a positive etiology, and being employed as peasants are all possible risk factors for pulmonary TB in Lishui City, Zhejiang Province.